Autoxidação de ésteres metílicos de ácidos graxos: estudo teórico-experimental - Albuquerque, Anderson dos Reis (2010)
In this work, computational chemistry calculations and thermal analysis experiments were performed in order to determine the oxidative stability of four fatty acid methyl esters (stearate, oleate, ricinoleate and linoleate), whose fatty chains may be inserted in oils and biodiesel. In the computational chemistry investigation the sequence of stabilities, based on the dissociation energy of the C-H bond was: C18:2 < C18:1 < C18:1;12-OH < C18:0, for the B3LYP 6-31G(d) and MP2 6-311++G(2d,p); and C18:2 < C18:1;12-OH < C18:1 < C18:0, for the B3LYP 6-311++G(2d,p). The spin density analysis allowed stating that the ricinoleate hydroxyl does not act as a pro-oxidizing, as the radicals formed in C-12 or OH are not stabilized by the unsaturation in C9, showing, thus, the behavior of a secondary alkyl alcohol in relation to these sites, whereas their allylic hydrogen display an energy similar to the oleate hydrogens. In the experimental investigation carried out TG, it was possible to observe the formation of hydroperoxides by means of the mass gain in an oxygen atmosphere for oleate, linoleate and ricinoleate, but only volatilization for the stearate. In this investigation, a small heating rate (2 ºC/min) was utilized. The kinetic calculations based on PDSC, in the dynamic and isothermal modes showed that the oxidation susceptibility is quite dependent of temperature, atmosphere and the method employed, being more critical in relation to the methyl ricinoleate. In the dynamic mode, in an air atmosphere at 110ºC, the relative susceptibility was 1 : 17 : 17 : 226 (C18:0 : C18:1 : C18:1;12-OH : C18:2). In an O2 atmosphere this proportion was 1 : 11 : 1 : 102. In the isothermal mode PDSC, at the same temperature, the proportion was 1 : 1230 : 1585 : 23001 in an air atmosphere, and 1 : 33 : 40 : 445 in an O2 atmosphere. Performing a structure/property relationship, the oxidation temperature determined at a heating rate of 10 ºC/min was shown to be strongly correlated with the BDE (C-H) obtained by DFT and MP2, confirming the relationship between the first exothermic event of PDSC in the dynamic mode and the C-H bond strength. Therefore, PDSC is shown as a accelerated testing technique able to determine the true oxidative stability of lipids, as it supplies information on the rate controlling step of auto-oxidation (L-H + R1● → L● + R1-H), whereas the Rancimat method does not supply such information. Ternary ester blends were made and their oxidative stabilities were assessed by means of PDSC in a synthetic air atmosphere. Four equations were obtained with high linear correlation coefficients (R2 > 0.98). A biodiesel representation model was also developed, expressing its main oxidation sites and molecular descriptors for several physico-chemical properties. This representation is expressed by the molecular formula Ca Hb H*c Hd** He***(O2)f (0H)g and shows as one of its advantages the easy display of biodiesel data, what makes more evident the study of structure/property relationship. Its application for the four FAME s and twenty-three blends allowed determining the oxidation temperature (OT) in an air atmosphere, based on the descriptors for allylic hydrogen (H*) and bis-allylic hydrogens (H**). From such model a program in language C was elaborated, whose input is the FAME mole fraction and whose output is the OT in a synthetic air atmosphere. Keywords: Auto-oxidation, FAME (fatty acid methyl esters), Biodiesel, PDSC, DFT.